Green Synthesis of Na abietate Obtained from the Salification of Pinus elliottii Resin with Promising Antimicrobial Action - Aline B. Schons; Patrícia Appelt; Jamille S. Correa; Mário A. A. Cunha; Mauricio G. Rodrigues; Fauze J. Anaissi (MDPI AG, 2023)
The growing concern about the emergence of increasingly antibiotic-r4esistant bacteria imposes the need to search and develop drugs to combat these microorganisms. This, combined with the search for low-cost synthesis methods, was the motivation for the elaboration of this work. Abietic acid present in the resin of Pinus elliotti var. elliotti was used to generate a sodium salt by salification. The synthesis route was low-cost, consisting of only two reaction steps at mild temperatures without toxic organic solvents, and eco-friendly and easy to conduct on an industrial scale. Sodium abietate (Na-C20H29O2) was characterized by mass spectrometry, infrared spectroscopy, elemental analysis, X-ray diffraction, scanning electron microscopy, and energy-dispersive spectroscopy. To perform the antimicrobial tests, the determination of minimum inhibitory concentration and the disk diffusion assay was performed. The results obtained showed that the salt Na abietate performed an antimicrobial action against the bacterial strains S. aureus, E. coli, L.monocytogenes, and S. enterica Typhimurium and the yeast C. albicans. The disk diffusion test showed a high inhibition potential against S. enterica compared to the standard antimicrobial tetracycline, as an inhibition index of 1.17 was found. For the other bacterial strains, the inhibition values were above 40%. The MIC test showed promising results in the inhibition of E. coli, L. monocytogenes, and C. albicans, indicating bacteriostatic activity against the first microorganism and bactericidal and fungicidal activities against the others. Therefore, the results showed the action of Na abietate as a possible effective antimicrobial drug, highlighting its sustainability within a circular economy.